A Positive (+ve) Postoperative Upper Instrumented Vertebra Tilt Angle (≥0°) Significantly Increases the Risk of Medial Shoulder and Neck Imbalance in Lenke 1 and 2 Adolescent Idiopathic Scoliosis Patients. Issue 12 (15th June 2020) - Kwan, Mun Keong; Lee, Sin Ying; Ch'ng, Pei Ying; Chung, Weng Hong; Chiu, Chee Kidd; Chan, Chris Yin Wei
Abstract : Study Design: Retrospective study. Objective: To investigate the relationship between a +ve postoperative Upper Instrumented Vertebra (UIV) (≥0°) tilt angle and the risk of medial shoulder/neck and lateral shoulder imbalance among Lenke 1 and 2 Adolescent Idiopathic Scoliosis (AIS) patients following Posterior Spinal Fusion. Summary of Background Data: Current UIV selection strategy has poor correlation with postoperative shoulder balance. The relationship between a +ve postoperative UIV tilt angle and the risk of postoperative shoulder and neck imbalance was unknown. Methods: One hundred thirty-six Lenke 1 and 2 AIS patients with minimum 2 years follow-up were recruited. For medial shoulder and neck balance, patients were categorized into positive (+ve) imbalance (≥+4°), balanced, or negative (−ve) imbalance (⩽−4°) groups based on T1 tilt angle/Cervical Axis measurement. For lateral shoulder balance, patients were classified into +ve imbalance (≥+3°) balanced, and −ve imbalance (⩽−3°) groups based on Clavicle Angle (Cla-A) measurement. Linear regression analysis identified the predictive factors for shoulder/neck imbalance. Logistic regression analysis calculated the odds ratio of shoulder/neck imbalance for patients with +ve postoperative UIV tilt angle. Results: Postoperative UIV tilt angle and preoperative T1 tilt angle were predictive of +ve medial shoulder imbalance. Postoperative UIV tilt angle and postoperative PT correction were predictive of +ve neck imbalance. Approximately 51.6% of patients with +ve medial shoulder imbalance had +ve postoperative UIV tilt angle. Patients with +ve postoperative UIV tilt angle had 14.9 times increased odds of developing +ve medial shoulder imbalance and 3.3 times increased odds of developing +ve neck imbalance. Postoperative UIV tilt angle did not predict lateral shoulder imbalance. Conclusion: Patients with +ve postoperative UIV tilt angle had 14.9 times increased odds of developing +ve medial shoulder imbalance (T1 tilt angle ≥+4°) and 3.3 times increased odds of developing +ve neck imbalance (cervical axis ≥+4°). Level of Evidence: 4 Abstract : Lenke 1 and 2 adolescent idiopathic scoliosis patients with positive postoperative upper instrumented vertebra tilt angle had 14.9 times increased odds of developing +ve medial shoulder imbalance (T1 tilt angle ≥+4°) and 3.3 times increased odds of developing +ve neck imbalance (cervical axis ≥+4°).